DE LA GUERRA Y DE LA PAZ. LA FILOSOFÍA DEL DERECHO EN TORNO A LOS DELITOS DE LESA HUMANIDAD Y UN POSIBLE ENCUENTRO CON LA PAZ (2016)
This paper, from the Philosophy of Law, aims to glimpse the standard and values plexus converge in today’s communities, these being inclusive sources, always used to establish the common good and peace so desired. Today, through this writing, are presented in the light of the Colombian reality some shortcomings and virtues that drench the current legal reality, and consequently the atrocities that have suffered our country, especially when it is a few days of signing a settlement agreement.This paper seeks to clarify the context involving Crimes against Humanity, its configuration and the both study and Political Ethics. To this, it is important to emphasize the analysis of the Rome Statute, putting this law (which we are so attached constitutionality) to the crucible of debate Dogmatic Penal, Criminology and Criminal Axiological or Statesman.